An Analysis of Teacher’s Strategies in Teaching Speaking Skills Through Cartoon Movie - Mutmainatul Mardiyah; Ade Maria Badriah (Candradimuka: Journal of Education, 2023)
Speaking is a language skill that must be mastered. Students' English speaking skills at the National English Centre have not been seen to be active. Researchers applied cartoon movies “Omar & Hana” as a medium in speaking activities to improve students' speaking skills. This study aims to find out whether the teacher's strategy of teaching speaking skills with cartoon movies can improve students' speaking skills, especially in the aspects of self-confidence and fluency at the lower level. The research method used in this research is descriptive qualitative by using observation, interviews, and documentation as research instruments. The population of this study was lower level at the National English Centre Jakarta which amounted to 28 students. Data collection by conducting direct observations in class and interviews. The results showed that students lacked confidence in speaking English. The environment greatly affects students' English language skills. The way the teacher teaches speaking skills is also very influential. Thus, the researcher concluded that the use of cartoon movies in teaching English was able to improve students' speaking skills, especially in aspects of self- confidence and fluency.